World travel : an irreverent guide - Bourdain, Anthony; Woolever, Laurie (Ecco, an imprint of HarperCollinsPublishers, 2021)
"A guide to some of the world's most fascinating places, as seen and experienced by writer, television host, and relentlessly curious traveler Anthony Bourdain"--